Growth performance of graded Brahman calves in selected areas of Mymensingh district (Journal of the Bangladesh Agricultural University, 2020)
The objectives of this study were to know the growth performance of graded Brahman calves, the phenotypic and genetic correlations between different growth traits and factors related to growth performance of Brahman graded calves in selected areas of Mymensingh district. Data on 422 Brahman graded calves were collected under the project entitled “Genetic improvement of indigenous cattle for beef production through crossing with Brahman cattle by farmers’ participatory breeding approach in Bangladesh” under the department of Animal Breeding and Genetics, BAU, Mymensingh. Statistical analyses of all the parameters were done using Statistical Analysis System (SAS). The growth performance and average daily gain of male calves were higher than those in female calves at different growth stages. The highest birth weight and weight at different stages of calves were higher in Bhabakhali and lowest in Dowhakhula area. Sex and area had significant effect (p